Anti-caries efficacy of the medicinal plant Miswak (Salvadora persica L.) and propolis Varnish on extracted human Premolar and Molar teeth - Ali Derakhshani; Sahereh Soltani; Parastoo Zarghami Moghaddam; Samaneh Mollazadeh; Manouchehr Teymouri (Journal of Medicinal Plants)
Background: Tooth decay is the result of the activity of cariogenic microorganisms that live in dental plaque. Among these, Streptococcus mutans is the main factor in the development and progression of dental tissue destruction. Objective: The study aims to investigate the anti-caries potential of a natural compound-based varnish against S. mutans on a set of dental specimens. Methods: Fifty-four extracted human molar and premolar specimens were procured from an outpatient clinic of pediatric dentistry, Bojnurd, Iran. These teeth were cast in a silicon putty and treated with a varnish made of propolis and miswak (from twigs of Salvadora persica L. tree) ethanolic extracts, followed by incubation in a harsh acidic medium (pH 2). Then, the density of samples, antibacterial activity, buffering capacity, and fluoride release were respectively investigated using radiography, disc diffusion and microdilution tests, and pH drop challenge in acetic acid solution (PH 4). Results: Overall, the varnishes protected the dental samples from dissolution in the acidic medium, as evidenced by the radiographic examination. The varnishes also exhibited remarkable antibacterial activity (inhibition zones of 3.2 ± 0.8 mm and 2.0 ± 0.2 mm for miswak and propolis varnish films), a considerable buffering capacity (pH increase from 4 to 7 within 5 minutes), and released fluoride (mean 85 µmoles). Conclusion: The application of natural compound-based varnish is strongly recommended for dental protection.